Coastal dilemma: Climate change, public assistance and population displacement. (February 2022) - Dasgupta, Susmita; Wheeler, David; Bandyopadhyay, Sunando; Ghosh, Santadas; Roy, Utpal
Highlights: Countries with populations and economic activity concentrated in low-lying coastal regions are vulnerable to sea-level rise. As the ocean advances inland, millions of coastal inhabitants will have to retreat, either by choice or force majeure. Linkages among environmental stress, public assistance and population change are assessed for coastal India and Bangladesh. Compensatory public assistance strongly dampens the migration response to rising environmental stress. Damage compensation should direct public resources to households that choose to relocate as the coastal threat mounts. Abstract: Linkages among climate change–related environmental stress, public assistance, and the spatial pattern of population change are assessed for neighboring coastal areas of India and Bangladesh. Environmental stress is measured using historical cyclone impacts, salinization, and land loss from erosion. Household migration decisions are based on current and expected future income streams in different locations. Rising environmental damage raises costs, but it may also induce increased public assistance that moderates or neutralizes those costs, diminishing migration incentives, even in areas hard-hit by climate change. Econometric estimates for the Sundarbans region shared by India and Bangladesh suggest that endogenous public assistance strongly dampens the migration response to rising environmental stress in both countries, though the assistance response and migration dampening are lower in Bangladesh. A broader analysis for the coastal region from India's Odisha State to eastern Bangladesh finds that present and past cyclone impacts are highly significant for explaining coastal population changes, although responses are lower in India because of lower environmental stress and greater public-assistance intensity. A counterfactual simulation suggests that, as a result of cyclones since 1970, the affected regions are 8–10% less populous in Bangladesh but only 2% less populous in India. The paper's findings motivate a discussion of the implications for alternative policy regimes as land erosion increases, and sea-level rise and salinization continue with climate change. After comparing the efficiency and equity of regimes that provide universal damage compensation or leave coastal households to fend for themselves, the paper suggests an alternative approach that focuses public resources on compensation for households that choose to relocate as the coastal threat mounts.